Analysis of Management Information System in Credit Decision Making: A Case Study of PT Bank Negara Indonesia Main Branch Office Manado - Manurung, Angel Ziw Floresia (PT FORMOSA CENDEKIA GLOBAL, 2025)
Management information system are very different from ordinary information system because these systems are used to analyze other information system that are applied to the active activities of the organization. The aim of this research is to find out the management information system in credit decision making at PT Bank Negara Indonesia Manado main branch office. This study uses a qualitative descriptive analysis. Based on the results of research conducted regarding the analysis of the management in granting credit at PT Bank Negara Indonesia, a conclusion can be drawn that the granting credit is carried out in full accordance with the framework but there are obstacles in collecting data due to the limited accounts provide by the OJK to parties bank. So the branch admin is obliged to correct the data provided. However, in general these two things are vulnerable to the problem of bad credit due to errors not only on the part of the debtor but sometimes arising from the wrong company in analyzing the eligibility of the prospective debtor. This problem can be prevented by having a control from the company. Control can be carried out through a management information system that can increase effectiveness in granting credit.